Chemical composition and bioactivity of essential oils and Ethanolic extracts of Ocimum basilicum L. and Thymus algeriensis Boiss. & Reut. from the Algerian Saharan Atlas - Maria Rezzoug; Boulanouar Bakchiche; Abdelaziz Gherib; Ascrizzi Roberta; FlaminiGuido; Özge Kilinçarslan; Ramazan Mammadov; Sanaa K. Bardaweel (BMC, 2019)
Abstract Background There is increasing interest in the pharmaceutical and food industries to substitute synthetic chemicals with naturally occurring compounds possessing bioactive properties. Plants are valuable sources of bioactive compounds. The present study investigates the chemical composition and antioxidant, antimicrobial, and anticancer activities of ethanolic extracts (EEs) and essential oils (EOs) from two species in the Lamiaceae family, Ocimum basilicum L. and Thymus algeriensis Boiss. & Reut., cultivated in the Algerian Saharan Atlas. Methods The total flavonoid contents of the plants' ethanolic extracts were determined by the aluminium chloride method, while the total phenols were determined using the Folin-Ciocalteu method. Essential oils were obtained by hydrodistillation of the aerial parts of the plants and were analysed by GC-MS. The free radical-scavenging ability and antioxidant potential of the plants' EEs and EOs were probed using the 2, 2-diphenyl-picrylhydrazyl radical-scavenging, ABTS radical-scavenging, ferric-reducing power and phosphomolybdenum assays. The antimicrobial activities were evaluated against several pathogens characteristic of gram-negative bacteria (three species), gram-positive bacteria (three species) and fungi (two species). The microdilution method was used to estimate the minimum inhibitory concentrations (MICs). The oils' anticancer potential against several cancer types was also studied using the MTT assay and reported as the toxic doses that resulted in a 50% reduction in cancer cell growth (LD50). Results Phenolic compounds in the EEs from both plants were analysed by HPLC and demonstrated a rich flavonoid content. Chemical analysis of the essential oil from Ocimum basilicum revealed 26 unique compounds, with linalool (52.1%) and linalyl acetate (19.1%) as the major compounds. A total of 29 compounds were identified in the essential oil from Thymus algeriensis, with α-terpinyl acetate (47.4%), neryl acetate (9.6%), and α-pinene (6.8%) as the major compounds. The ethanolic extracts and essential oils from both plants exhibited moderate antioxidant activities and moderate to weak antimicrobial activities. Furthermore, anticancer activities against the examined human cancer cell lines were associated with only the EOs from both plants, with LD50 values ranging between 300 and 1000 μg/mL. Conclusion The results suggest that the bioactive compounds found in the ethanolic extracts and essential oils from Ocimum basilicum and Thymus algeriensis, with diverse antioxidant, antimicrobial and anticancer activities, may have beneficial applications in nutraceutical and pharmaceutical technologies.